Activity concentrations of natural radioactivity and radiological dosimetry of virgin and agricultural soils in Kano State, Nigeria - Olabimtan, Samuel Olugbenga; Chifu, Ebenezer Ndikilar; Nasir, Maharaz; Hafeez, Hafeez Yusuf (Universitas Sebelas Maret, 2024)
Natural radiation exposure from varying number of radionuclides in the soil is a major source of radiation dose around the world. These radionuclides are taken up by plants and transferred to crops leading to their concentrations in foods/crops. Activity concentrations of natural radioactivity in uncultivated and agricultural soils were analyzed in six rice producing Local Government Areas (Bagwai, Bunkure, Dambatta, Garko, Kura and Wudil) of Kano State, Nigeria using gamma-ray Spectrometer with Sodium-Iodide Scintillation detector. The activity concentrations, in Bq.kg-1, of 40K, 238U and 232Th ranged from 262.03 – 848.64 (mean: 547.76 ± 27.16), 11.27 – 65.14 (mean: 31.60 ± 3.32) and BDL – 25.11 (mean: 8.75 ± 0.50) in virgin soils; and 249.01 – 1098.91 (mean: 509.51 ± 25.21), 0.97 – 59.92 (mean: 25.46 ± 2.73) and 3.28 – 24.13 (mean: 12.26 ± 0.70) in agricultural soils in the study areas. Concentrations of 40K and 238U in virgin soils were generally higher than their corresponding values recorded in agricultural soils but higher values of 232Th were obtained in agricultural soils. The mean values of Radium equivalent activity, 86.29 Bq.kg-1 (virgin soils), and 82.22 Bq.kg-1 (agricultural soils) were lower than the world average value: 370 Bq.kg-1. The average Hazard indices (external and internal) values of virgin soils (0.233, 0.3210) and agricultural soils (0.222, 0.291) were all less than unity, which is the maximum permissible limit. However, slightly higher values of Hazard indices were obtained in virgin soils. The mean absorbed dose rate (D), annual effective dose equivalent (AEDE) and excess lifetime cancer risk (ECLR) were: 42.73 nGyh-1, 0.0524 mSv.y-1 and 0.119 x 10-3, respectively for virgin soils and, 40.41 nGyh-1, 0.0500 mSv.y-1 and 0.113 x 10-3 respectively for agricultural soils. These estimated values for both virgin and agricultural soils are all less than the world average of 59.0 nGyh-1, 0.070 mSv.y-1 and 0.29 x 10-3. Slightly lower values of D, AEDE and ECLR in agricultural soils is as a result of continuous human activities due to farming practices.